1975
DOI: 10.1002/qj.49710142808
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of the ozone concentration near the stratopause

Abstract: Using measurements from two instruments on the Nimbus 4 satellite comparisons between ozone concentration and temperature have been made at levels near Imb during an occasion of stratospheric warming.High correlation exists between ozone concentration and temperature. Good agreement has been found with a photochemical model which incorporates ' classical ' oxygen photochemistry together with reactions involving OH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(74 citation statements)
references
References 19 publications
(1 reference statement)
1
73
0
Order By: Relevance
“…Because of this effect, future tropical ozone levels show even further decline at the end of the 21st century compared to near-present values. The slowing of photochemical ozone loss reactions caused by the cooling in the stratosphere (Barnett et al, 1975;Jonsson et al, 2004) contributes to a smaller degree to the overall TOC evolution (Zubov et al, 2013). Li et al (2009) showed that the BDC acceleration plays a crucial role in future ozone recovery and spatial distribution.…”
Section: Ozone Responsementioning
confidence: 99%
“…Because of this effect, future tropical ozone levels show even further decline at the end of the 21st century compared to near-present values. The slowing of photochemical ozone loss reactions caused by the cooling in the stratosphere (Barnett et al, 1975;Jonsson et al, 2004) contributes to a smaller degree to the overall TOC evolution (Zubov et al, 2013). Li et al (2009) showed that the BDC acceleration plays a crucial role in future ozone recovery and spatial distribution.…”
Section: Ozone Responsementioning
confidence: 99%
“…In the daytime mesosphere, catalytic ozone depletion by odd hydrogen has to be considered in addition to the Chapman cycle. The anticorrelation of ozone and temperature is mainly due to the temperature dependence of the rate coefficients of the Reactions (R3) and (R2) (Craig and Ohring, 1958;Barnett et al, 1975).…”
Section: S Studer Et Al: Climatology Of the Diurnal Ozone Variationmentioning
confidence: 99%
“…Anthropogenic emissions of GHGs are also expected to influence stratospheric ozone concentrations, both through their dynamical and their chemical effects. GHG-induced cooling of the stratosphere is expected to contribute to an increase in the rate of ozone recovery by slowing gas-phase ozone loss reactions (Barnett et al, 1975;Jonsson et al, 2004). A warming troposphere and associated changes in wave activity propagation from the troposphere into the stratosphere are also predicted to speed up the Brewer-Dobson circulation (Butchart et al, 2006).…”
Section: Introductionmentioning
confidence: 99%